2012
DOI: 10.1016/j.it.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

How mesenchymal stem cells interact with tissue immune responses

Abstract: Mesenchymal stem cells (MSCs), also called multipotent mesenchymal stromal cells, exist in almost all tissues and are a key cell source for tissue repair and regeneration. Under pathological conditions, such as tissue injury, these cells are mobilized towards the site of damage. Tissue damage is usually accompanied by proinflammatory factors, produced by both innate and adaptive immune responses, to which MSCs are known to respond. Indeed, recent studies have shown that there are bidirectional interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
402
1
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(431 citation statements)
references
References 99 publications
(143 reference statements)
10
402
1
18
Order By: Relevance
“…in the presence of low levels of pro-inflammatory cytokines such as IFN-g and TNF-a) can promote immune responses and that this involves the production of chemokines that recruit lymphocytes to sites of inflammation but insufficient levels of either NO (for murine MSCs) or IDO (for human MSCs) to inhibit T cell proliferation. Moreover, murine MSCs in which iNOS has been genetically ablated or pharmacologically inhibited have been shown to strongly enhance T cell proliferation (25,30,40,41). Further optimization of cytokine combinations and/or concentrations may be necessary to enhance therapeutic effects of syn-MSCs in this model.…”
Section: Discussionmentioning
confidence: 99%
“…in the presence of low levels of pro-inflammatory cytokines such as IFN-g and TNF-a) can promote immune responses and that this involves the production of chemokines that recruit lymphocytes to sites of inflammation but insufficient levels of either NO (for murine MSCs) or IDO (for human MSCs) to inhibit T cell proliferation. Moreover, murine MSCs in which iNOS has been genetically ablated or pharmacologically inhibited have been shown to strongly enhance T cell proliferation (25,30,40,41). Further optimization of cytokine combinations and/or concentrations may be necessary to enhance therapeutic effects of syn-MSCs in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that for MSC to suppress T cells, the MSC must first be activated by proinflammatory cytokines [18,19,23,60]. The major cytokine known to ''license'' MSC to become immune modulatory has been identified as IFN-g [36,60].…”
Section: Msc Activation By Ifn-c Required For Full Immune Suppressivementioning
confidence: 99%
“…Numerous studies have investigated the underlying mechanisms that drive the immune modulatory properties of both human and mouse MSC [16,[18][19][20]. In human MSC, the reported pathways of immune suppression by MSC include the indoleamine 2,3-deoxygenase (IDO) [21,22], cyclooxygenase [23][24][25], TGF-b [26], soluble IL-1Ra [27,28], soluble MHC [29,30], and the PD-L1 pathways [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Interaction and treatment of stem cells with inflammatory cytokines may also help enhance their therapeutic efficacy. This is well brought out in a mouse model with GvHD induced disease [26].…”
Section: Mscs In Tb and Other Infectionsmentioning
confidence: 86%